(untitled) (Canadian Dermatology Today, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant tumour suppressor syndrome associated with benign and malignant tumours, predominantly affecting the skin and nervous system. NF1, the most prevalent neurocutaneous syndrome, and the focus of this review, has a frequency of 1/1,900-1/3,500 people worldwide. Disease manifestations can present at birth and emerge with age, negatively impacting multiple clinical domains and imparting a profound impact on a patient’s quality of life and life expectancy. Given its progressive nature and marked clinical variability, NF1 warrants a multidisciplinary approach to management and treatment.